The Scenario of Local Educational Administration in Form of City Municipality - Yingcharoensomsuk, Sunita; Suwanmanee, Sinchai (Hatyai Academic Journal, 2023)
This study aimed to developing and evaluating of the scenario of local educational administration in form of city municipality with mixed methods research, a hierarchical model with 3 phases: Phase 1, qualitative research methods, the determination of future issues and trend events from in-depth interviews with 21 experts by specific selection methods were used and the instrument used was a semi-structured interview form. Phase 2, using the Delphi technique to confirm future issues and trend events from 21 experts, used a selective method and the instrument used was the content analysis criterion questionnaire for mean, median of 3.50 or more, and the interquartile range from 1.50 down. Phase 3, quantitative research methods to evaluate the scenario of local educational administration in form of city municipality, the samples were 685 from director of the bureau of education, school administrators, teacher as a section chief and teacher by purposive sampling. The research findings revealed that: 1) According to the opinions of experts, synthesis of data from interviews with qualified persons. Scenario and trend events to be defined as a scenario of the education administration of local governments in from of the city municipality, which groups according to the consensus of the experts. As follows: scenario 1: The system and education administration consisted of 5 trend events, scenario 2: Administrator Quality (National/Province/Municipality) consisted of 4 main trend events and 32 sub-trend events, scenario 3: Quality of teacher and educational personnel consisted of 4 main trend events and 21 sub-trend events, scenario 4: Student quality consisted of 11 trend events, scenario 5: Courses consisted of 2 main trend events and 33 sub-trend events, scenario 6: Media, equipment, innovation and educational technology consisted of 2 main trend events and 8 sub-trend events, scenario 7: Creating the learning society consisted of 3 main trend events and 9 sub-trend events, and scenario 8: Educational, network consisted of 8 main trend events. Draft of the scenario includes 8 scenarios 127 trend events, and 123 trend events pass expert consensus judging criteria. 2) The scenario of local educational administration in form of city municipality, the model’s indicators and components are consistent with empirical data by analyzing second-order confirmatory factors. It found that there were the values of Chi-square at 63.68 df that was equal to 60 GFI and AFGI were 0.99 and 0.97 respectively. The square root of SRMR was 0.009, and the square root of RMSEA was 0.009